pegegog 2022
DOI: 10.47750/pegegog.12.04.27
|View full text |Cite
|
Sign up to set email alerts
|

Achievement motivation and learning behavior of students during COVID-19 pandemic: gender differences

Abstract: This study aimed to describe and compare the achievement motivation and learning behavior based on male and female students in Indonesia. Respondents have involved 902 female high school students and 637 male high school students using the cluster random sampling technique. Data were collected using a scale of achievement motivation and learning behavior with has a validity coefficient of items in the range of 0.362 to 0.724, and each had Cronbach's alpha reliability of 0.811 and 0.866; data analyzed by descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…This discrepancy can be attributed to the mode of learning where the integration of AR technology happened. The online class brought by the pandemic made an impact on the motivation of male students to learn making it less than that of the female students (Atmoko et al, 2022). However, it was found that both male and female respondents have the same positive feedback contrary to the mixed literature that one has greater positive feedback compared to the other (Ahmad et al, 2005;Kimbrough et al, 2013;Hamza and Shah, 2014;Kongaut and Bohlin, 2016;Hsu, 2017;Chen et al, 2017;Dirin et al, 2019).…”
Section: Gendermentioning
confidence: 96%
“…This discrepancy can be attributed to the mode of learning where the integration of AR technology happened. The online class brought by the pandemic made an impact on the motivation of male students to learn making it less than that of the female students (Atmoko et al, 2022). However, it was found that both male and female respondents have the same positive feedback contrary to the mixed literature that one has greater positive feedback compared to the other (Ahmad et al, 2005;Kimbrough et al, 2013;Hamza and Shah, 2014;Kongaut and Bohlin, 2016;Hsu, 2017;Chen et al, 2017;Dirin et al, 2019).…”
Section: Gendermentioning
confidence: 96%